E Hāpai Ana i ā Mātou Uara mā roto i Te Mana Whakahaere Raraunga hei Whakapūmau i te Mana Motuhake = Utilising our values through Te Mana Whakahaere Raraunga to enact Māori data sovereignty : a research report presented in partial fulfilment of the requirements for the degree of Master of Health Science (Māori Health) at Massey University, Palmerston North, New Zealand - Te Whata, Felicity Jayne (Massey University, 2022)
Whānau Ora has evolved from a policy position to a practice that provides pathways for whānau to achieve their own moemoeā. Across multiple projects and programmes Te Tihi o Ruahine Whānau Ora Alliance (Te Tihi) capture large amounts of whānau data. As kaitiaki within our data environment, it is crucial that we ensure the understanding of Māori data sovereignty, actualise it into usable tools, maintain a strength-based approach to data analysis, and implement robust security protocols. Additionally, maintaining the rights of whānau (those whom the data is about) regarding use, access, and dissemination is essential to Māori data sovereignty. This research project seeks to understand Māori data sovereignty through the experience of a Whānau Ora provider by exploring the development of our data governance and management framework, Te Mana Whakahaere Raraunga, and its impact within Te Tihi as well as the wider mahi we engage with. Interviews from key informants who hold expertise in the unique knowledge of Te Tihi and/or Māori data sovereignty were thematically analysed with a deductive approach based on our organisation’s values. The key findings of this research will be illustrated by examples of Māori data sovereignty such as within Kāinga Whānau Ora and Āta - our (data and communications) COVID-19 response, demonstrating how Te Mana Whakahaere Raraunga assists Te Tihi in upholding our organisational values that support our hapori and whānau.
First Māori Health specialisation in the Master of Health Science degree
Keywords: Indigenous data sovereignty; New Zealand; Mana raraunga; Māori Masters Thesis; 451204 Te mana motuhake o ngā raraunga Māori (Māori data sovereignty)